Egalitarian teams in a military hirearchy: a study of the formation of the Royal Air Force senior leadership team - Jupp, J A (Cranfield University, 2015)
This thesis is a participant observer and action research case study of the Royal Air Force’s efforts to improve its senior leadership from2007 to 2010. It addresses the research question: what are the conditions required to establish an egalitarian team in a military hierarchy? It examines the establishment of the Senior Leadership Team, designed to operate as a forum for the dissemination of the leader’s intent, dissemination of information, and generation of ideas. The literature review argues there are four bodies of relevant knowledge that derive from the research question: forming large teams, use of power, changing culture, and building interpersonal trust. From the literature, two models are considered, one for formation of large teams and another for establishing an egalitarian culture in a hierarchy. The theoretical position to examine the case study from is a combination of the four areas and the two models. The conclusions emphasise the need for leadership and facilitation to deal with the issues of behaviour; charade of cooperation; homogeneity and heterogeneity; effects of power, particularly on trust; group size paradox; and creating open discussion. The thesis argues, in this context, culture is akin to organisational identity and it examines how culture might be changed and sustained in a strict hierarchical organisation to ensure open discussion where all opinions are equal. The thesis identifies the fundamental importance of interpersonal trust for large informational or consultative teams that hold a different culture to their host organisation. In conclusion, the thesis argues that the models examined do not provide an adequate framework for this case study and tentatively puts forward a 7-factor model representing the conditions required to establish an egalitarian team in a military hierarchy.
Keywords: Defence leadership; Leadership; Royal Air force